Hate Speech in India: Contemporary Legal Challenges and Responses - Das, Dipshreeya (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
This article examines the legal challenges of addressing hate speech in India, focusing on the balance between free speech and public order, as well as the protection of vulnerable communities. It reviews existing legal frameworks, including constitutional provisions under Articles 19(1)(a) and 19(2), statutory laws like Sections 153A, 295A, and 505(1) of the Indian Penal Code, and Section 69A of the Information Technology Act. Key judicial pronouncements, such as Shreya Singhal v. Union of India, are analyzed to highlight regulatory complexities. The study identifies social media proliferation, political exploitation, and legal ambiguities as critical contemporary issues. Using a qualitative research methodology, the article proposes reforms including clearer definitions of hate speech, stronger enforcement mechanisms, and new laws targeting online hate speech and political incitement. It also advocates for enhanced public awareness and education. These measures aim to curb hate speech while upholding democratic values and ensuring societal harmony, contributing to the discourse on digital governance and legal responses in India. In light of the increased incidents of hate speech in India and the legal challenges surrounding it, this article seeks to analyze the existing frameworks and propose necessary reforms.